INDIGENOUS CONSERVATION OF CROP GENETIC RESOURCES IN THE UPPER EAST REGION OF GHANA - Essel, E.; Galley, J. J.; Mohammad, H. D.; Imoro, A-W. M.; Sackey, I.; Adonadaga, M-G. (UDS International Journal of Development, 2022)
Traditional farmers are aware of crop genetic erosion and use various indigenous conservation methods in their farming systems to protect and sustain crop production. The objective of the study was to assess the indigenous conservation methods and practices for some selected crop genetic resources (CGRs) in the Kassena-Nankana and Bolgatanga areas of Ghana. Data was gathered with the aid of a questionnaire, secondary data and first-hand observations. The primary subject for the study were farmers. The study communities were selected by convenient sampling and based on key informants’ information. Two hundred farmers from ten communities each from Kassena-Nankana and Bolgatanga municipalities served as subjects in this study. The results revealed that, farmer’s choice of CGRs for cultivation was based on food preference, marketability, and early maturing crops among others. Maize, millet, rice and groundnut were the most cultivated crops in the two study areas making up 15-25%. In both areas, 52-65% of the farmers were males and 35-48% females. Use of preserved seeds as planting materials was practiced by 41-49% of farmers, 21-26% purchased their planting materials and 21-23% practiced a combination of the two. The indigenous conservation practices were pot preservation, bunch hanging, bottle preservation, sack preservation and local silos/barns. Methods employed to achieve CGRs conservation included the use of ashes from burnt plant residue and plant parts and plant extracts. The findings of the study revealed that some indigenous practices are moderately practiced by the farmers in the surveyed areas to ensure CGRs conservation and food security. Keywords: Conservation practices, Crop, Genetic resources, Farmers, Indigenous, Ghana